Kafkaesque Guilt – Existential Guilt and the Law of Hospitality on the Basis of Kafka’s Novel das Schloss - Grätzel, Stephan (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Based on Paul Ricoeur’s ideas, the paper presents the “Kafkaesque guilt” as a modern, unconscious and diffused form of existential guilt, in which we owe our existence to others and therefore we are guilty of it. Existential guilt as mutual indebtedness manifests itself fundamentally in the right to hospitality. One can deal with it only in a narrative. The guilt for breaking the law of hospitality becomes clear in Kafka’s novel Das Schloss.